Alternative realities - Plantinga, Carl R. (Quick takes., 2021)
"Movies are uniquely capable of creating and displaying fantastical worlds. With the rise of CGI came the ascendance of animated fantasy, superhero, and science fiction films. The movies are also capable of representing unique subjective experiences; a movie can be an "experience recorder." Somewhat paradoxically, however, movies are thought to have a strong connection to everyday reality and to have roots in realism. Alternative Realities explores the complex intersection between movies, reality, and fantasy; between subjective and objective representation. It shows that even the most surreal fantasies ground their images, sounds, and narratives in quotidian reality. On the other hand, even the most realistic documentaries and realist dramas rely on creative structures that are products of the human imagination. This combination of realism and imagination, of the objective and the subjective, is the key to the power of movies"--